The Voice Track multiband single-channel modified Wiener-filter noise reduction system for cochlear implants: patients' outcomes and subjective appraisal. (2nd August 2016) - Guevara, Nicolas; Bozorg-Grayeli, Alexis; Bebear, Jean-Pierre; Ardoint, Marine; Saaï, Sonia; Gnansia, Dan; Hoen, Michel; Romanet, Philippe; Lavieille, Jean-Pierre
Abstract: Objective : The aim of this study was to evaluate the potential improvements of speech perception and sound quality provided by a multiband single channel noise-reduction algorithm based on the modified Wiener-filter adapted to cochlear implant sound processing. Design : This study was a longitudinal trial with a repeated-measures design. Outcome measures were performed on the first day when the noise reduction feature was provided and after a one month habituation period. Objective measures included pure-tone thresholds and vocal audiometry assessments. Speech perception was measured in quiet and in the presence of two types of noise: a stationary speech shaped noise and a two-talker cocktail noise. Subjective sound quality was assessed using a ten item questionnaire. Study Sample : Thirteen post-lingual deaf adults, experienced users of a cochlear implant system, took part in this study. Results : The noise-reduction algorithm provided a benefit for the perception of speech presented in a stationary speech shaped noise and an overall improvement in subjective sound quality ratings. Conclusions : It was shown that a single channel noise reduction system based on a modified Wiener-filter approach can improve speech in noise perception performance and subjective sound quality in cochlear implant patients.